Meiotic Genes Are Enriched in Regions of Reduced Archaic Ancestry. (21st April 2017) - Jégou, B.; Sankararaman, S.; Rolland, A.D.; Reich, D.; Chalmel, F.
Abstract: About 1–6% of the genetic ancestry of modern humans today originates from admixture with archaic humans. It has recently been shown that autosomal genomic regions with a reduced proportion of Neanderthal and Denisovan ancestries (NA and DA) are significantly enriched in genes that are more expressed in testis than in other tissues. To determine whether a cellular segregation pattern would exist, we combined maps of archaic introgression with a cross-analysis of three transcriptomic datasets deciphering the transcriptional landscape of human gonadal cell types. We reveal that the regions deficient in both NA and DA contain a significant enrichment of genes transcribed in meiotic germ cells. The interbreeding of anatomically modern humans with archaic humans may have introduced archaic-derived alleles that contributed to genetic incompatibilities affecting meiosis that were subsequently purged by natural selection.